Many Rivers to Cross: Social Identity, Cognition and Labour Mobility in Rural India - Sébastien Michiels; Christophe Jalil Nordman; Suneha Seetahul (Institute of Labor Economics (IZA), 2021)
By considering the case of rural South India, this study analyses whether individual skills and personality traits are able to facilitate labour market mobility of disadvantaged groups in the presence of constraining social structures. We use an individual panel dataset built on two household surveys carried out in 2010 and 2016-2017 in Tamil Nadu. We explore the relationship between individual cognitive skills (Raven, literacy and numeracy scores), personality traits (Big Five Inventory) and earnings mobility. We first assess the extent of gender and caste-based labour market segmentation using transition matrices. Then, we take advantage of intra-group heterogeneity in terms of cognitive skills and personality traits to explore whether these personal characteristics can enable individuals to overcome rigid social structures. Results show that personality traits are important determinants of labour mobility. Nonetheless, we observe a strong rigidity of the labour market structure in terms of gender and caste, and its relative stillness over time.
Keywords: J24; J31; J71; O12; 330; personality; cognitive skills; income mobility; occupational transition; Tamil Nadu; India